Design and Performance Analysis of Inverter Using ECRL, MERL and PFAL - Raman; Ramnish Kumar (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2017)
In this paper, different low energy design techniques are analyzed to overcome the shortcoming of traditional circuits. An inverter circuit is used as a reference circuits to compare three adiabatic logic designs like ECRL, MERL and PFAL. The ECRL, MERL and PFAL designed inverter circuits are simulated by using mentor graphics VLSI design software Pyxis _v10.5_5_201606075 and the obtained results are compared in terms of rise time, fall time, transistor count, delay, slew rate etc. Finally, I calculated the delays, Slew rate and other parameter of PFAL based circuit results better as compared to ECRL and MERL.